2010
DOI: 10.1080/08952841.2010.518882
|View full text |Cite
|
Sign up to set email alerts
|

Aging and Sexuality: How Much Do Gynecologists Know and Care?

Abstract: Enhanced knowledge and healthy attitudes toward aging sexuality can help promote the perception that full sexual expression is part of the entire extent of adulthood. We sought to determine gynecologists' knowledge and attitude regarding sexuality in older women. A total of 141 gynecologists in five hospitals responded to the survey: Aging Sexual Attitude and Knowledge Scale (ASKAS). No correlation was found between respondents' knowledge and attitude (r = .06, p = .54); no correlation found between respondent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 11 publications
1
23
1
1
Order By: Relevance
“…Because very little in known about this topic, our results begin to address this gap in understanding. When compared with previous provider samples, the knowledge of aging sexuality scores for providers in this study indicated less knowledge than U.S. graduate nursing students (Luketich, 1991), Turkish physicians (Dogan et al, 2008), and U.S. OB/GYNs (Langer-Most & Langer, 2010). However, compared with nursing home staff and older adult care workers, this sample's knowledge was better (White, 1982).…”
Section: Discussionmentioning
confidence: 41%
See 2 more Smart Citations
“…Because very little in known about this topic, our results begin to address this gap in understanding. When compared with previous provider samples, the knowledge of aging sexuality scores for providers in this study indicated less knowledge than U.S. graduate nursing students (Luketich, 1991), Turkish physicians (Dogan et al, 2008), and U.S. OB/GYNs (Langer-Most & Langer, 2010). However, compared with nursing home staff and older adult care workers, this sample's knowledge was better (White, 1982).…”
Section: Discussionmentioning
confidence: 41%
“…This is a self-report measure that contains 61 items, 35 of which measure knowledge. The Aging Sexuality Knowledge and Attitudes Scale has been used with professional (Bouman, Arcelus, & Benbow, 2007;Dogan et al, 2008;Langer-Most & Langer, 2010) and community (Hillman & Stricker, 1996;White & Catania, 1982) (Davis, 1988). Content and criterion validity have been demonstrated for this measure as well (Davis, 1988).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The same survey with Brazilian university students (20) analyzed the results based on the answer of each question , which made it impossible to compare the data with this study, that analyzed the global result of the questionnaire. However, another American study with gynecologists (21) had an average score of 81 on the American ASKAS scale, in which the scores range from 26 to 182, representing 35.2% of the possible score, what showed that the population of the present study had a more favorable attitude towards the sexuality of the elderly than the gynecologists. In literature, studies assessing the knowledge and attitude of the patients were not found, only surveys with students and health professionals (21,22) .…”
Section: Discussionmentioning
confidence: 81%
“…However, another American study with gynecologists (21) had an average score of 81 on the American ASKAS scale, in which the scores range from 26 to 182, representing 35.2% of the possible score, what showed that the population of the present study had a more favorable attitude towards the sexuality of the elderly than the gynecologists. In literature, studies assessing the knowledge and attitude of the patients were not found, only surveys with students and health professionals (21,22) . These results are the first to be obtained from the application of this instrument in this population.…”
Section: Discussionmentioning
confidence: 81%